Smart farming IoT based management during post Covid-19 - Elmy Johana, Mohamad; Kian Sek, Tee; Choon, Chewchang; Omar Mohd Faizan, Marwah; Mimi Mohaffyza, Mohamad; Noor Nazihah, Mohd Noor; Ruzairi, Abdul Rahman; Jaysuman, Pusppanathan; Mohd Hafiz, Fazalul Rahiman; Yasmin, Abdul Wahab; Suzanna, Ridzuan Aw (Institute of Electrical and Electronics Engineers Inc., 2022)
The aim of this project is to construct portable smart farming management tools that could be helpful for the farmer involved in the pineapple industry. The project also aims to focus on the productivity of the plant by varying the fertilizer contents. During the Covid-19 pandemic that impacts all industries especially the agriculture industry, the farmers had an issue related to precision in terms of monitoring the soil condition of their crops due to limitations on the mobility of people across borders and lockdowns are contributing to labor shortages. Therefore, this study expected to look at the possibilities of the Smart Farming Management Tool Internet-of-Things based to be implemented in helping farmers to keep on track of the soil conditions in their crops via smartphones.